2009
DOI: 10.1097/cej.0b013e328305a0c9
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cancer and the risk of endometrial cancer

Abstract: To investigate the relationship between family history of cancer in first-degree relatives and the risk of endometrial cancer, we carried out a large multicentre case-control study in Italy between 1992 and 2006, including 454 endometrial cancer cases and 908 controls admitted in hospital for acute, non-neoplastic diseases. Conditional logistic regression was used to estimate odds ratios (ORs) and corresponding 95% confidence intervals (CI). Relative to women with no family history of uterine cancer, the ORs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…The existence of a genetic mutation in the known or unknown cancer genes that were not included in the test cannot be excluded and inherited susceptibility remains a possibility. A simple family history of ovarian cancer will increase the risk for the same disease three to four times, while endometrial cancer risk is increased by around two times according to existing literature [37,38]. On the other hand, testing positive for a cancer predisposing genetic mutation can confer extremely high risks for both ovarian cancer and endometrial cancer.…”
Section: Interpretation Of Test Resultsmentioning
confidence: 85%
“…The existence of a genetic mutation in the known or unknown cancer genes that were not included in the test cannot be excluded and inherited susceptibility remains a possibility. A simple family history of ovarian cancer will increase the risk for the same disease three to four times, while endometrial cancer risk is increased by around two times according to existing literature [37,38]. On the other hand, testing positive for a cancer predisposing genetic mutation can confer extremely high risks for both ovarian cancer and endometrial cancer.…”
Section: Interpretation Of Test Resultsmentioning
confidence: 85%
“…9 Two studies estimated risk of endometrial cancer stratified by age at diagnosis of endometrial cancer in a first-degree relative. 12,17 A large cohort study 17 reported a higher risk of endometrial cancer for women with a first-degree relative with younger age at diagnosis of endometrial cancer, whereas a small casecontrol study 12 reported no evidence of a difference in endometrial cancer risk by age at diagnosis in the relative. Only one study estimated risk of endometrial cancer by the number of affected first-degree relatives and reported a higher risk of endometrial cancer for women with a higher number of affected first-degree relatives.…”
Section: Resultsmentioning
confidence: 95%
“…Nine studies 6,7,9,10,[12][13][14][15]17 estimated an association between family history of colorectal cancer and risk of endometrial cancer (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations